Assessing The Javan Leopard Presence and Prey Abundance: Insights from Camera Trap Surveys in Meru Betiri National Park East Java Indonesia - Kholiq, Nur; Sulistyowati, Hari; Tabah Wibisono, Hariyo; Asmoro Lelono; Retno Wimbaningrum; Sattya Arimurti; Arif Mohammad Siddiq; Adi Sucipto (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
The use of incomplete or imbalanced data in ecological modelling and conservation planning can lead to inaccurate predictions due to limitations in detection methods. Therefore, obtaining comprehensive and precise empirical data on species presence and availability, particularly prey species is essential. This study aims to: (1) identify the presence of Javan leopards and their potential prey species, and (2) estimate the relative abundance indices (RAI) of each prey species. Using camera trap data from the Meru Betiri National Park (MBNP) survey conducted in 2024, we recorded 24 species, including the Javan leopard, and identified seventh potential prey species. We estimated relative abundance of each potential prey species was determined by dividing the number of individuals recorded in independent photos or videos by the total number of trap days and multiplied by 100. The result of RAI analysis indicated that the most abundant prey species in the study area was the long-tailed macaque, with an RAI value of 44.16 individuals per 100 trap-days, banteng was the least frequently detected species, appearing in only three independent images, with an RAI value of 0.23. The presence of Javan leopards, a charismatic flagship species, highlights the ecological significance of this area and provides valuable data for biodiversity management, serving as a foundation for future research and conservation efforts.